The relationship of shyness to self-concept among upper elementary school students in the Area Al-Qasr Education Directorate - Mawadeh, Rozeen Khalaf; Ibrahim, Mikail (Journal of Educational and Psychological Sciences, 2023)
The present study aimed to identify the shyness relationship with Self concept, and Self concept regarding gender and class among students at the high primary stage in the educational department of Al-Quser district in Al-Karak governorate. In order to achieve the study goals, a randomly sample of (772) students were selected, (382) of them were males, and (390) were females. Shyness scale, University of California, Los Angeles , and the scale of Self – concept of Berce – Hares, were applied. The results showed that there was a negative statistical relationship between shyness and Self- concept. Moreover, there were significant statistical differences between males and females in their responses on the shyness scale in favor of females, whereas there were no significants statistical differences between males and females in their responses on the scale of the the Self – concept. For the grade variable, the results showed that there significant statistical differences on the shyness scale in favor of the seventh and eighth grades. Moreover, the study results showed that the students of the ninth and tenth grades attained higher scores on the self- concept scale.